2005
DOI: 10.1309/aqxr-6b2q-pugd-638c
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Glutathione S-Transferase a in Clear Cell Renal Cell Carcinoma

Abstract: To determine its diagnostic value, we evaluated glutathione S-transferase alpha (GST-alpha) expression in a large number of renal cell carcinomas (RCCs). GST-alpha messenger RNA (mRNA) levels from 70 renal neoplasms were analyzed with complementary DNA (cDNA) microarray chips containing 21,632 cDNA clones. Furthermore, 348 primary renal tumors and 24 metastatic RCCs were subjected to immunohistochemical analysis with a GST-alpha-specific antibody. GST-alpha mRNA was elevated significantly (11.4-fold) in a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
0
17
2
Order By: Relevance
“…[28][29][30][31][32][33][34][35][36][37][38] Renal cell carcinoma marker antibody, CD10, glutathione S-transferase-a and others have shown specificity for clear cell renal cell carcinoma, 28,29 a-Methylacyl CoA racemase is expressed in papillary renal cell carcinoma, 30 whereas parvalbumin, b-defensin 1 and most recently KIT are used as markers for chromophobe renal cell carcinoma and oncocytoma. [31][32][33] However a marker with sufficient specificity to differentiate between chromophobe renal cell carcinoma and oncocytomas has not yet been unequivocally established.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36][37][38] Renal cell carcinoma marker antibody, CD10, glutathione S-transferase-a and others have shown specificity for clear cell renal cell carcinoma, 28,29 a-Methylacyl CoA racemase is expressed in papillary renal cell carcinoma, 30 whereas parvalbumin, b-defensin 1 and most recently KIT are used as markers for chromophobe renal cell carcinoma and oncocytoma. [31][32][33] However a marker with sufficient specificity to differentiate between chromophobe renal cell carcinoma and oncocytomas has not yet been unequivocally established.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sarcomatoid RCC with S-100 protein positivity may resemble a malignant peripheral nerve sheath tumor. In this instance, other markers frequently expressed in CRCC, such as CD10, p504S, epithelial membrane antigen, glutathione-S-transferase a, and RCC marker, should be considered to prevent a misinterpretation [4][5][6]10,21].…”
Section: Discussionmentioning
confidence: 99%
“…Twentyfour samples of normal renal tissues were also included. Tissue microarray blocks were constructed with a 1.5 mm tissue core or 2 1.0-mm tissue cores from each case as previously reported [21].…”
Section: Methodsmentioning
confidence: 99%
“…To date, several studies have demonstrated the diagnostic value by immunohistochemical staining of these new markers on hundreds of cases. For example, by immunohistochemical staining, glutathione S-transferase α was found highly expressed in clear-cell RCC 18 and α-methylacyl-CoA racemase in papillary RCC. 19 Some of these markers will be especially useful in distinguishing histology with more subtle differences, such as the differences between type 1 and type 2 papillary RCC 20 or between oncocytoma and chromophobe RCC (T.B.T., unpublished data, 2007).…”
Section: Differentially Expressed Genes In Different Subtypes Of Renamentioning
confidence: 99%